100 years of banking in Asia and Africa, 1863-1963 - Tyson, Geoffrey CIE (London, National and Grindlays Bank, 1963)
Primarily this book is a history of the Bank, its difficulties and setbacks as well as its growth, but running through it both purposely and of necessity is the thread of the economic and political developments of the countries
Bibliographical footnotes.
osc 15/05/2018
Loans
Keywords: Banking; Banking - histroy; Banking - 100 years; Banks and banking; Africa; Asia